Interfaith Collaboration in Waste Management through Black Soldier Fly Cultivation in Tulungagung - Fadhilah, Nur; Ivantri, Rohmah (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
This study explores a community-based approach to organic waste management using Black Soldier Fly (BSF) cultivation in Tulungagung. Conducted within a Community Engagement Program, the project involved interfaith communities using a participatory method that combined training, practice, and sustainability assessment. Participants engaged in hands-on BSF cultivation and waste sorting activities, which improved their understanding and practices in organic waste management. Quantitative and qualitative evaluations revealed enhanced awareness, skills, and behavioral change among participants. The initiative also fostered stronger interreligious social networks, contributing to a more inclusive and sustainable local environment. This study highlights the potential of integrating technology, religion, and community participation in a replicable waste management model. Future initiatives are encouraged to explore economic incentives and technological improvements to further enhance BSF effectiveness.